2016
DOI: 10.1136/bjsports-2015-095841
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-intensity interval training on cardiometabolic health: a systematic review and meta-analysis of intervention studies

Abstract: The current review clarifies the cardiometabolic health effects of high-intensity interval training (HIIT) in adults. A systematic search (PubMed) examining HIIT and cardiometabolic health markers was completed on 15 October 2015. Sixty-five intervention studies were included for review and the methodological quality of included studies was assessed using the Downs and Black score. Studies were classified by intervention duration and body mass index classification. Outcomes with at least 5 effect sizes were sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

53
485
13
30

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 563 publications
(581 citation statements)
references
References 121 publications
(63 reference statements)
53
485
13
30
Order By: Relevance
“…Similarly, Earnest et al [54] observed similar improvements in the MetS Z -score and the number of MetS risk factors between overweight males who participated in HIT and MCT. Due to methodological differences across studies (i.e., sex; age; initial health, weight and fitness status; prescribed medication; type and intensity of exercise, or interval duration; length of the exercise program) and the impact of such differences on outcomes [5557], it is difficult to draw general conclusions. These and other possible factors need to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Earnest et al [54] observed similar improvements in the MetS Z -score and the number of MetS risk factors between overweight males who participated in HIT and MCT. Due to methodological differences across studies (i.e., sex; age; initial health, weight and fitness status; prescribed medication; type and intensity of exercise, or interval duration; length of the exercise program) and the impact of such differences on outcomes [5557], it is difficult to draw general conclusions. These and other possible factors need to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…However, the correlations between change in sleep duration and change in insulin sensitivity‐related outcomes indicate some role for increasing sleep duration. While this study certainly had limitations (no control group, no direct assessment of insulin sensitivity in response to a glucose challenge (Leproult et al., ), the extent to which fasting glucose levels were reduced was similar to that observed in individuals who were overweight or obese and undertook 12 weeks of high‐intensity interval training (Batacan, Duncan, Dalbo, Tucker, & Fenning, ). Although comparisons between the two interventions are difficult because of the differences in populations studied and reporting of the data, one might speculate that a sleep extension intervention may be as effective in improving fasting glucose and insulin levels as exercise, specifically high‐intensity interval training.…”
Section: Discussionmentioning
confidence: 54%
“…Contudo, a interpretação dessa diferença deve ser cautelosa, pois a magnitude das alterações se encontram na margem de erro para medições de circunferên-cia de cintura 41 . Os achados desta meta-análise divergem com os resultados encontrados pelos de Batacan et al 42 . Nesse estudo foram avaliados 65 ensaios clínicos randomizados e não randomizados, onde foi encontrado melhora significativa para o HIIT na circunferência de cintura e percentual de gordura corporal, quando realizados ≥12 semanas, na população obesa e/ou com sobrepeso.…”
Section: Discussionunclassified